Establishment Of Dna Protocols For Genetic Studies Of Junonia Orithya Metion (Lepidoptera: Nymphalidae) - Muhamad Ikhwan, Idris (Universiti Malaysia Sarawak, (UNIMAS), 2006)
This study was aimed at establishing a protocol for DNA work and genetic Studies such as molecular systematic, evolution, ecology, behavior and development on the butterflies in general. Result of the study to establish the protocol while trying to identify potential genetic markers is presented. By taking J.orithya metion as an example for the sample. the extraction protocol on the thorax, using CTAB method was successfully applied on both fresh and long dry-preserved specimens deposited in the Insect Reference collection of the Faculty of Resource Science and Technology Museum. Universiti Malaysia Sarawak (UNIMAS). Amplification on the extracted DNA targeting cytochrome b gene of mitochondrial DNA were managed to be obtained for fresh samples but failed for museum specimens. Thus, CTAB method can be applied to extract DNA of insect in general and butterfly in particular while the optimum protocols for DNA extraction and amplification are still in progress to carry on.